THE IMPACT OF DIVORCE IN CONTEMPORARY ISLAMIC LAW: CHILDREN'S RIGHTS AND PARENTS' OBLIGATIONS AFTER DIVORCE - Putra, Dedisyah; Martua Nasution; Disry Desky (Universitas Islam Indonesia, 2025)
Purpose – This study aims to examine the impact of divorce from a contemporary Islamic legal perspective, focusing on the fulfillment of children's rights and parental obligations post-divorce. The background of this research is driven by the increasing number of divorce cases in Indonesia, which often leave behind child custody issues. Therefore, an in-depth study of how Islamic and positive laws protect children is necessary. Method - This study employs a normative juridical approach, analyzing statutory regulations, Islamic law, and contemporary interpretations. This analysis is also supported by contemporary Islamic legal theory, which emphasizes child protection in modern law to assess the alignment between religious norms and national regulations. Findings – The study's findings indicate that although divorce ends a marriage, parental responsibilities, both material and immaterial, remain unchanged. Fathers are obligated to provide child support, and mothers play a primary role in childcare. Both parents are obligated to ensure their child's education, emotional stability, and moral development. Furthermore, religious courts play a central role in ensuring the fulfillment of children's rights through custody decisions, although implementation is often hampered by economic disparity, emotional conflict between parents, weak legal awareness, and a lack of post-divorce oversight mechanisms. This demonstrates the gap between legal norms and social reality, which has implications for child welfare. Research contribution/limitations – This study emphasizes the role of religious courts in protecting children's rights through custody arrangements and enforcing post-divorce maintenance obligations in Indonesia. However, obstacles such as economic disparity, interparental conflict, and social stigma often undermine the effectiveness of fulfilling children's rights. Originality/value – This study contributes to the literature by offering solutions through strengthening parental legal awareness, increasing cooperation between parents even after divorce, and improving institutional mechanisms. These efforts are crucial for ensuring the best interests of children and providing input for policymakers, legal practitioners, and researchers focusing on family law and child welfare.